Comparison of the efficacy of intralesional measles, mumps, and rubella vaccine with intralesional vitamin D3 for the treatment of extragenital warts in pediatric age group (5–18 years) - Jafir Ahmed; Ramesh Kumar Kushwaha; Avinash Sharma; Morish Agarwal; Neha Sharma; Suresh Kumar Jain (Indian Journal of Paediatric Dermatology, 2023)
Introduction: Warts are benign skin growths caused by human papillomavirus. Traditional methods of treatment usually include destructive modalities which are painful and scar-forming. Such modalities have disadvantage of recurrence. Consequently, immunotherapy is introduced to overcome these problems. Aims and Objectives: To study the comparative efficacy of intralesional measles, mumps, and rubella (MMR) vaccine with intralesional Vitamin D3 for the treatment of extragenital warts in the pediatric age group (5–18 years). Materials and Methods: Seventy-two immunocompetent patients aged between 5 and 18 years with multiple extragenital warts (2 or more) were enrolled and divided randomly into two groups (Group A and Group B). Group A and Group B received intralesional MMR vaccine and Vitamin D3, respectively, in the largest wart present. The injections were repeated every 2 weeks for a maximum of four injections. Results: Complete response (CR) in injected warts in Group A is seen in 25 (83.3%) patients, partial response (PR) in 3 (10%), and no or inadequate response (NR) in 2 (6.67%) patients. CR is seen in 23 (76.66%) patients of Group B, PR in 4 (13.33%) and no or NR in 3 (10%) patients. CR in distant warts in 22 (73.33%) patients in Group A and 20 (66.66) patients in Group B. Conclusion: Both MMR vaccine and Vitamin D3 are safe, efficacious, and less traumatic to the patients for multiple warts in comparison with destructive modalities.